Graphical simulation of numerical algorithms : an approach based on code instrumentation and Java technologies - Balsa, Carlos (2012)
We want to create a working tool for mathematics teachers and a corresponding learning tool for students, namely a graphical simulator of mathematical algorithms (GraSMa). To achieve it we try two different strategies. We started by annotate manually the original algorithm with inspector functions. Now we are testing a new approach that aims to automatically annotate the original code with inspector functions. To achieve this we are developing a language translator module that enables to comment automatically any code written in Octave language. The run of the annotated code gated by one of these two ways, records in a XML (eXtensible Markup Language) file everything that happened during the execution. Subsequently, the XML file is parsed by a Java application that graphically represents the mathematic objects and their behaviour during execution. The final application will be accessed on-line through a website (WebGraSMa) which is currently under development. In this paper we report and discuss about the procedures followed and present some intermediate results.